Time is of the essence when it comes to forest bioenergy. Issue 2 (14th December 2021) - Norton, Michael; Walloe, Lars; Brack, Duncan; Booth, Mary; Jones, Michael B.
Abstract : Debate continues in this journal on the climate impacts of burning woody biomass from forests. A recent review by Cowie et al. (2021, GCB Bioenergy, 13(8), 1210–1231) addressed what it called 'misconceptions' in papers by us and other authors that examined issues of carbon debt and when burning forest biomass for energy could have a net climate benefit. This letter re‐emphasizes the critical importance of the time dimension in assessing impacts, and takes particular issue with Cowie et al's lack of concern over substantial delays in reducing emissions and increasing the risks of crossing climate tipping points.